Systematic Analysis of Gene Expression Profiles Controlled by hnRNP Q and hnRNP R, Two Closely Related Human RNA Binding Proteins Implicated in mRNA Processing Mechanisms - Cappelli, Sara; Romano, Maurizio; Buratti, Emanuele (Frontiers in Molecular Biosciences, 2018)
Heteregeneous ribonucleoproteins (hnRNPs) are a family of RNA-binding proteins that take part in all processes that involve mRNA maturation. As a consequence, alterations of their homeostasis may lead to many complex pathological disorders, such as neurodegeneration and cancer. For many of these proteins, however, their exact function and cellular targets are still not very well known. Here, we focused the attention on two hnRNP family members, hnRNP Q and hnRNP R, that we previously found affecting TDP-43 activity both in Drosophila melanogaster and human neuronal cell line. Classification of these two human proteins as paralogs is suported by the high level of sequence homology and by the observation that in fly they correspond to the same protein, namely Syp. We profiled differentially expressed genes from RNA-Seq and generated functional enrichment results after silencing of hnRNP Q and hnRNP R in neuroblastoma SH-SY5Y cell line. Interestingly, despite their high sequence similarity, these two proteins were found to affect different cellular pathways, especially with regards to neurodegeneration, such as PENK, NGR3, RAB26, JAG1, as well as inflammatory response, such as TNF, ICAM1, ICAM5, and TNFRSF9. In conclusion, human hnRNP Q and hnRNP R may be considered potentially important regulators of neuronal homeostasis and their disruption could impair distinct pathways in the central nervous system axis, thus confirming the importance of their conservation during evolution.